1996
DOI: 10.1073/pnas.93.20.11019
|View full text |Cite
|
Sign up to set email alerts
|

A developmental switch in lymphocyte homing receptor and endothelial vascular addressin expression regulates lymphocyte homing and permits CD4+ CD3- cells to colonize lymph nodes.

Abstract: In adult mice, the dominant adhesion molecules involved in homing to lymph nodes are L-selectin homing receptors on lymphocytes and the peripheral lymph node addressins on specialized high endothelial venules. Here we show that, from fetal life through the rst 24 hr of life, the dominant adhesion molecules are the mucosal addressin MAdCAM-1 on lymph node high endothelial venules and its counterreceptor, the Peyer's patch homing receptor, integrin a4(87 on circulating cells. Before birth, 40-70%o of peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
181
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(191 citation statements)
references
References 55 publications
(46 reference statements)
8
181
1
Order By: Relevance
“…In this process members of the TNF/LT induce the expression of stromal and endothelial MAdCAM-1, which is required for the initial recruitment of lymphocytes to the forming PP anlage (29,30). In Nkx2-3 2/2 mice MAdCAM-1 expression is preserved in PPs until the perinatal period, in agreement with previous data demonstrating HEV-associated MAdCAM-1 in neonatal mLNs (17).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this process members of the TNF/LT induce the expression of stromal and endothelial MAdCAM-1, which is required for the initial recruitment of lymphocytes to the forming PP anlage (29,30). In Nkx2-3 2/2 mice MAdCAM-1 expression is preserved in PPs until the perinatal period, in agreement with previous data demonstrating HEV-associated MAdCAM-1 in neonatal mLNs (17).…”
Section: Discussionsupporting
confidence: 91%
“…The MAdCAM-1 to PNAd switch in HEVs of mutant PPs resembles the physiological switch in pLNs of wild-type mice during the first weeks of life in which Nkx2-3 is not appreciably expressed (29). This suggests that Nkx2-3 functions as a repressor of the MAdCAM-1 to PNAd exchange.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…They were the first described innate lymphoid cells; our subset functioned to establish HEVs, as well as to induce the structural domains in lymph nodes and Peyer patches (79,80). These cells are present in fetal mice, but we could not see them in adults.…”
Section: The Thymus Thymic Maturation B Lymphocyte Development Hommentioning
confidence: 99%
“…These cells are present in fetal mice, but we could not see them in adults. Amazingly, we found that they gained access to incipient lymph nodes that expressed the Peyer patch addressin MAdCAM-1 rather than the lymph node addressin PNAd; the HEVs then switched soon after birth to their normal addressin expression for life, after lymph node architecture was established (79,81,82).…”
Section: The Thymus Thymic Maturation B Lymphocyte Development Hommentioning
confidence: 99%